2018
DOI: 10.30969/acsa.v14i3.965
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química e microbiológica do leite de cabra produzido em Petrolina-PE

Abstract: Objetivou-se avaliar a qualidade físico-química e microbiológica do leite de cabra produzido em propriedades de Petrolina-PE.   Para as análises físico-químicas utilizou-se equipamento Master Classic Complete AKSO®, com exceção da acidez, utilizando-se o método Dornic. Foram realizadas análises de contagem de bactérias aeróbias mesófilas (BAM), número mais provável de coliformes (NMP) totais e termotolerantes. Três amostras apresentaram inadequação quanto ao teor de acidez, nove para índice crioscópico e três … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
16

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
1
4
0
16
Order By: Relevance
“…In this study, the raw milk from Cariri, Paraíba, presented high mesophilic counts in dairies A, B, and C. Only dairy D was within the patterns, but with values close to the limits established by legislation. Such findings corroborate the values presented by Coelho et al (2018), who found mesophiles values from 5,3x10 2 to 5,3x10 5 . The same authors state that such values are due to the lack of hygiene during milking and the delay in the cooling process.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the raw milk from Cariri, Paraíba, presented high mesophilic counts in dairies A, B, and C. Only dairy D was within the patterns, but with values close to the limits established by legislation. Such findings corroborate the values presented by Coelho et al (2018), who found mesophiles values from 5,3x10 2 to 5,3x10 5 . The same authors state that such values are due to the lack of hygiene during milking and the delay in the cooling process.…”
Section: Resultssupporting
confidence: 92%
“…The total coliforms are composed of bacteria from the Enterobacteriaceae family that can ferment lactose and produce gas when incubated at 35-37ºC per 48 hours (Mendes et al, 2009). The thermotolerant coliforms are characterized by their capacity to ferment lactose with acid and gas production at the temperature of 45°C (Coelho et al, 2018). These microorganisms constitute a subgroup of total coliforms, in which their presence indicates the probability of contamination with fecal material (Mendes et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Coelho et al (2018) a acidez pode ser utilizada como indicador do estado de conservação do leite em função da relação entre disponibilidade de lactose e produção de ácido láctico por ação microbiana, acarretando aumento na acidez e diminuição no teor de lactose.…”
Section: Resultsunclassified
“…A indústria de produtos lácteos de origem caprina na região semiárida do Nordeste brasileiro apresenta um crescente desenvolvimento na última década (COELHO et al, 2018), sendo o queijo um dos produtos mais processados por apresentar uma demanda pela população, bem como por ser um alimento de grande valor nutritivo (POVEDA, 2013;LIMA et al, 2019). Entretanto, como resultado da produção de queijo está a geração de uma grande quantidade de soro de leite, um coproduto que quando lançado sem nenhum tratamento nos efluentes industriais gera problemas ambientais (CAMPOS et al, 2004;LADEIRA et al, 2020).…”
Section: Introductionunclassified